2017
DOI: 10.1038/s41598-017-10070-1
|View full text |Cite
|
Sign up to set email alerts
|

A DNA aptamer efficiently inhibits the infectivity of Bovine herpesvirus 1 by blocking viral entry

Abstract: Bovine herpesvirus 1 (BoHV-1) is an important pathogen of domestic and wild cattle responsible for major economic losses in dairy and beef industries throughout the world. Inhibition of viral entry plays a crucial role in the control of BoHV-1 infection and aptamers have been reported to inhibit viral replication. In this study, nine DNA aptamers that target BoHV-1 were generated using systemic evolution of ligands by exponential enrichment. Of the nine candidates, aptamer IBRV-A4 exhibited the highest affinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…However, clinical trials have not yet been done to use them as therapeutic molecules. Similarly, Xu et al, 2019 , Xu et al, 2017 demonstrated that specific DNA aptamers can inhibit the production of Bovine herpesvirus 1 through blocking nucleocytoplasmic shuttling and inhibiting the infectivity of the virus by blocking viral entry. The developed aptamers exhibited high affinity and specificity for Bovine herpesvirus 1 with a Kd value of 3.519 nM and significantly reduced viral replication.…”
Section: Application Of Aptamers In the Targeted Drug Delivery And Treatment Of Animal Diseasesmentioning
confidence: 97%
See 1 more Smart Citation
“…However, clinical trials have not yet been done to use them as therapeutic molecules. Similarly, Xu et al, 2019 , Xu et al, 2017 demonstrated that specific DNA aptamers can inhibit the production of Bovine herpesvirus 1 through blocking nucleocytoplasmic shuttling and inhibiting the infectivity of the virus by blocking viral entry. The developed aptamers exhibited high affinity and specificity for Bovine herpesvirus 1 with a Kd value of 3.519 nM and significantly reduced viral replication.…”
Section: Application Of Aptamers In the Targeted Drug Delivery And Treatment Of Animal Diseasesmentioning
confidence: 97%
“… Bai et al (2019) 27 DNA aptamer Competitive voltammetric aptasensor for azlocillin β-lactam antibiotic. Chinnappan et al (2020a) 28 DNA aptamer Detection of Bovine herpesvirus 1 Xu et al, 2019 , Xu et al, 2017 ssDNA aptamers 29 ssDNA aptamer Detection of SARS coronavirus nucleocapsid protein Cho et al (2011) 30 ssDNA aptamer HN protein of Bovine Parainfluenza Virus type 3 Cheng et al (2018) 31 ssDNA aptamer Detection of avian influenza H5Nx whole viruses Nguyen et al (2016) 32 ssDNA aptamer Detection of Muscovy duck parvovirus Lu et al (2018) 33 ssDNA aptamer Detection of Staphylococcus aureus Baumstummler et al (2014) 34 ssDNA aptamer An enzyme linked aptamer for the detection of P48 protein of M. bovis Fu et al (2014) 35 ssDNA aptamer Detection of TB from sputum samples Rotherham et al (2012) 36 ssDNA aptamer Analytical assay for detection of brevetoxin. Tian et al (2016) 37 ssDNA aptamer Combined the aptamer with electrochemical SPR to develop an aptasensing platform for detection of ampicillin in real time.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of animal welfare and agriculture progress, several aptamers have been developed to control viral diseases. To block host entry by Bovine herpesvirus 1 (BoHV-1), Xu et al used SELEX to develop a DNA aptamer against the BoHV-1 virus that efficiently inhibited viral entry of BoHV-1 in bovine kidney cells, indicating that this aptamer is a potential therapeutic agent for control of BoHV-1 infection in cattle 259 . DNA aptamers targeting the S10 protein of grass carp reovirus were also developed and further applied to block viral entry, providing a potential treatment tool for viral diseases in fish 260 .…”
Section: Potential For Aptamer Technology In Communicable Disease Therapeuticsmentioning
confidence: 99%
“…In 2017, Xu et al selected a DNA aptamer called IBRV-A4 targeting bovine herpesvirus 1. This herpesvirus is the cause of infectious bovine rhinotracheitis, a disease characterized by damage to the upper respiratory tract, but that can also be responsible for abortions in pregnant cows and encephalitis in calves [ 93 ]. The aptamer from Xu et al may provide a potential diagnostic tool, and also exhibits antiviral properties by preventing the virus from entering cells when administered within 30 min of infection [ 93 ].…”
Section: Therapeutic Applications In Veterinary Medicinementioning
confidence: 99%